2017
DOI: 10.2495/eres170081
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Damage Assessment of Rc Building With the Transfer Slab System

Abstract: Over the past decade, several studies investigated behavior aspects of irregular structures and limitations of seismic code provisions for such class of buildings. This paper investigates the dynamic and seismic behavior of buildings employing thick transfer slab between two different structural systems, representing podium and upper tower. The shape of these structures is commonly dictated by either aesthetic or functional considerations that often preclude simplicity or regularity. The purpose of this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This work tackled the displacement incompatibility between connected walls that imposed high in-plane strains in the slabs and beams connecting the tower wall above the podium interface level. Elassaly and Nabil [7] investigated seismic behavior of 2-D RC structures using transfer slab models. The aim was to determine the seismic damage of these types of structures compared to regular ones.…”
Section: Engineering Research Journal (Erj)mentioning
confidence: 99%
“…This work tackled the displacement incompatibility between connected walls that imposed high in-plane strains in the slabs and beams connecting the tower wall above the podium interface level. Elassaly and Nabil [7] investigated seismic behavior of 2-D RC structures using transfer slab models. The aim was to determine the seismic damage of these types of structures compared to regular ones.…”
Section: Engineering Research Journal (Erj)mentioning
confidence: 99%
“…It was found that podium can impose different boundary conditions on tower walls with respect to their proximity to the center of the podium or the location along the supporting transfer plate. (Elassaly & Nabil, 2017) inspected seismic behavior of two dimensional reinforced concrete structures using transfer slab models. In their research, six natural ground motions were used.…”
Section: Introductionmentioning
confidence: 99%